Multiphase Converter with Currentless Sensing Technique - Yahaya J.A.F.; Mansor M.; Sulaiman A.H.; Reyasudin Basir Khan M. (Engineering and Scientific Research Groups, 2023)
Electric inductors; MATLAB; Balancing currents; High-frequency harmonics; Inductor voltage; Matlab/Simulink simulation; Multiphase converters; Phase-inductors; Resistor capacitors; Sensing techniques; DC-DC converters